Pengaruh Moderasi Kesiapan Teknologi Pada Penggunaan E-Learning di Kalangan Pelajar Studi Kasus : SMP Sutomo 1 Medan - Budi, Setia; Panjaitan, Erwin Setiawan; Nurjanah, Sofiana (Universitas Multi Data Palembang, 2025)
This research aims to investigate the moderating effect of technology readiness on the use of E-learning among students, with a focus on a case study at SMP Sutomo 1 Medan. E-learning has become an increasingly popular method of learning, especially in the context of distance education. The Delone and McLean theory is used as the theoretical framework to examine the use of E-Learning and technology readiness, consisting of variables such as optimism, innovativeness, discomfort, and insecurity as moderation variables. The research method is quantitative, and the data source is obtained through a questionnaire from 332 students at SMP Sutomo 1 Medan. Data analysis is conducted using SmartPLS 3 and hypothesis testing. The research results indicate accepted hypotheses in the relationships between Information Quality and Intention to use, Service Quality and Intention to use, Information Quality and User Satisfaction, Service Quality and User Satisfaction, User Satisfaction and Net Benefit, and the optimism variable moderating System Quality on Intention to use. Rejected hypotheses include System Quality with Intention to use, and the moderation variables of innovativeness, discomfort, and insecurity that do not influence the relationship between System Quality and User Satisfaction